The Development of People’s Participation in Local Political Election: A Case Study of Nakhon Pathom Municipality Nakhon Pathom Province - Tosurat, Patcharamon (Rajapark Journal, 2024)
This research aims to: 1) investigate the context and problems of an election in Nakhon Pathom Municipality; 2) explore factors affecting the decision to exercise their right to vote; and 3) find guidelines to explain to voters in the community how to exercise their right to vote. A mixed-methods approach was employed to collect data, including a questionnaire and an in-depth interview. The statistics used in this study contained frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The results related to the context and problems of an election in Nakhon Pathom Municipality, which was 19.5 square kilometers, indicated that the administrative areas were divided into 9 sub-districts with a total population of 72,753, containing 34,445 males and 38,308 females. Moreover, the overall exploration of factors affecting the decision to exercise their right to vote was at the highest level. Given guidelines to explain to people in the community how to exercise their right to vote, there were two guidelines selected, which were vote guidelines and election cognition.